Influence of tree shape and evolutionary time‐scale on phylogenetic diversity metrics. Issue 10 (9th December 2015) - Mazel, Florent; Davies, T. Jonathan; Gallien, Laure; Renaud, Julien; Groussin, Mathieu; Münkemüller, Tamara; Thuiller, Wilfried
Abstract : During the last decades, describing, analysing and understanding the phylogenetic structure of species assemblages has been a central theme in both community ecology and macro‐ecology. Among the wide variety of phylogenetic structure metrics, three have been predominant in the literature: Faith's phylogenetic diversity (PDFaith ), which represents the sum of the branch lengths of the phylogenetic tree linking all species of a particular assemblage, the mean pairwise distance between all species in an assemblage (MPD) and the pairwise distance between the closest relatives in an assemblage (MNTD). Comparisons between studies using one or several of these metrics are difficult because there has been no comprehensive evaluation of the phylogenetic properties each metric captures. In particular it is unknown how PDFaith relates to MDP and MNTD. Consequently, it is possible that apparently opposing patterns in different studies might simply reflect differences in metric properties. Here, we aim to fill this gap by comparing these metrics using simulations and empirical data. We first used simulation experiments to test the influence of community structure and size on the mismatch between metrics whilst varying the shape and size of the phylogenetic tree of the species pool. Second we investigated the mismatch between metrics for two empirical datasets (gut microbes and global carnivoran assemblages). We show that MNTD and PDFaith provide similar information on phylogenetic structure, and respond similarly to variation in species richness and assemblage structure. However, MPD demonstrate a very different behaviour, and is highly sensitive to deep branching structure. We suggest that by combining complementary metrics that are sensitive to processes operating at different phylogenetic depths (i.e. MPD and MNTD or PDFaith ) we can obtain a better understanding of assemblage structure.